2018
DOI: 10.1186/s13640-018-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle classification based on images from visible light and thermal cameras

Abstract: We propose novel vehicle detection and classification methods based on images from visible light and thermal cameras. These methods can be used in real-time smart surveillance systems. To classify vehicles by type, we extract the headlight and grill areas from the visible light and thermal images. We then extract texture characteristics from the images and use these as features for classifying different types of moving vehicles. We also extract several features from images obtained at night and during the day,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 24 publications
(22 reference statements)
0
24
0
Order By: Relevance
“…However, since vehicles are moving on the road, heat can be captured by the windshield or tyres which might not be applicable to this paper, as the vehicles are stationary in a parking lot. Based on another study, the thermal camera was used to classify vehicles types using features extracted from the front end of the vehicle [11]. Classification of vehicle types using thermal camera performed poorly since a thermal camera shows features in pseudo colours based on generated heat.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since vehicles are moving on the road, heat can be captured by the windshield or tyres which might not be applicable to this paper, as the vehicles are stationary in a parking lot. Based on another study, the thermal camera was used to classify vehicles types using features extracted from the front end of the vehicle [11]. Classification of vehicle types using thermal camera performed poorly since a thermal camera shows features in pseudo colours based on generated heat.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thermal cameras were largely used on images or videos collected during dusk or night conditions [8]. A combination of visual spectrum images for daylight and thermal images for night conditions were utilised to enable detection in varying illumination conditions [11]. There is scarce of the literature identifying vehicles only using the thermal camera in varying illumination and environmental conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results obtained shows 92.5% accuracy over a testing dataset. Nam and Nam (2018) had proposed a surveillance system for detecting and classifying of vehicles during the day and at night time. The various parameters used for the feature extraction was textures, entropy, homogeneity, energy and contrast.…”
Section: Related Workmentioning
confidence: 99%
“…For automobile tracking based on surveillance video, it is essential to extract the primary vehicle features such as plate number, color, and size from a video frame. Nam et al [8] classified the types of vehicles as, amongst others, SUVs, sedans, and RVs using images from visible light and thermal cameras. Suryatali et al [9] reported a scheme for determining the direction and size of automobiles using Kalman filters.…”
Section: Automobile Recognizing and Trackingmentioning
confidence: 99%